Die unklare Leberraumforderung - Roderburg, Christoph; Loosen, Sven H.; Bruners, Philipp; Luedde, Tom (DMW - Deutsche Medizinische Wochenschrift, 2019)
Unknown liver lesions represent a common clinical challenge, for example in the context of routine ultrasound examinations of primary care physicians. There are different data on the prevalence of primary liver lesions in the literature. As such, a forensic autopsy series described focal liver lesions in about 50 % of all examined men between 35 and 69 years of age with an increasing incidence for older people. In the diagnostic work-up of unclear liver lesions, a careful distinction between lesions that occur in asymptomatic and healthy individuals and are benign in over 95 % of cases, and lesion found in patients with pre-existing malignant, inflammatory or cirrhotic disease must be made. The main goal in the diagnosis of unclear liver lesions is to prove the benignity of the lesion and to exclude a malignant cause as reliably as possible. In case of benign lesions, an attempt should be made to achieve an exact classification. The most common benign focal liver lesions include liver cysts, focal fatty liver deposition or sparing, haemangiomas, focal calcifications, focal nodular hyperplasia (FNH), nodular regenerative hyperplasia, biliary hamartomas (von-Meyenburg complexes) and hepatocellular adenomas. Abscesses, inflammatory infiltrations or pseudotumors as well as sites of extramedullary haematopoiesis are observed much less frequently. Among the most frequent malignant focal liver lesions are metastases of other tumor entities such as colorectal cancer or pancreatic adenocarcinoma as well as hepatocellular carcinoma (HCC) and cholangiocellular carcinoma (CCA). Other entities such as hepatic lymphomas or mesenchymal malignant neoplasia are extremely rare.
Keywords: Leberraumforderung; Hämangiom; FNH; Leberzelladenom; Bildgebung